2015
DOI: 10.1111/asj.12402
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of elite rescue dogs by somatic cell nuclear transfer

Abstract: The objective of the present study was to compare the efficiency of two oocyte activation culture media to produce cloned dogs from an elite rescue dog and to analyze their behavioral tendencies. In somatic cell nuclear transfer procedure, fused couplets were activated by calcium ionophore treatment for 4 min, cultured in two media: modified synthetic oviduct fluid (mSOF) with 1.9 mmol/L 6-dimethylaminopyridine (DMAP) (SOF-DMAP) or porcine zygote medium (PZM-5) with 1.9 mmol/L DMAP (PZM-DMAP) for 4 h, and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Artificial activation of the reconstructed embryos was induced, and, immediately after activation, the embryos were transferred into oviducts of recipient dogs. Consequently, the resulting cloned puppy had the same nuclear and mitochondrial genetic information as the cell donor and oocyte donor, respectively [ 8 29 37 42 ]. Since that first cloned dog, a variety of cloned dogs have been produced, and it has been reported that dog cloning using the SCNT technique can be successfully performed regardless of the sex (male [ 36 ] and female [ 25 ]), age (fetus [ 18 ], young adult [ 36 ], and old [ 24 ]), or breed (Afghan hound [ 25 36 ], miniature poodle [ 24 ], beagle [ 18 29 ], Labrador Retriever [ 35 43 ], Pekingese [ 46 ], German Shepherd [ 30 42 ], Sapsaree [ 23 ], and Gyeongju Donggyeong dog [ 8 ]) of the cell donor.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial activation of the reconstructed embryos was induced, and, immediately after activation, the embryos were transferred into oviducts of recipient dogs. Consequently, the resulting cloned puppy had the same nuclear and mitochondrial genetic information as the cell donor and oocyte donor, respectively [ 8 29 37 42 ]. Since that first cloned dog, a variety of cloned dogs have been produced, and it has been reported that dog cloning using the SCNT technique can be successfully performed regardless of the sex (male [ 36 ] and female [ 25 ]), age (fetus [ 18 ], young adult [ 36 ], and old [ 24 ]), or breed (Afghan hound [ 25 36 ], miniature poodle [ 24 ], beagle [ 18 29 ], Labrador Retriever [ 35 43 ], Pekingese [ 46 ], German Shepherd [ 30 42 ], Sapsaree [ 23 ], and Gyeongju Donggyeong dog [ 8 ]) of the cell donor.…”
Section: Introductionmentioning
confidence: 99%
“…The canine SCNT technique has been notably improved since Snuppy, the first cloned dog, was born in 2005 (Lee et al., ). This achievement made canine SCNT applicable to various fields such as conservation of endangered species (Choi et al, ; Jang et al, ; Kim et al, ; Oh et al., ), elite working dogs (Choi et al., ; Oh et al., , ) and animal model researches (Hong et al., ; Kim et al., , ).…”
Section: Application Of Canine Scntmentioning
confidence: 99%
“…Cloning dogs by SCNT is a highly effective way of producing dogs with exceptional skills, as they are identical to those of cell donor dogs except the mitochondrial genome. For instance, the elite cloned dogs with high ability for drug detection in airport/quarantine areas or rescuing human in disaster fields have been successfully generated (Kim et al, , ; Oh et al., , ). Furthermore, their ability to sniffing drugs was evaluated (Choi et al., ), and all of the cloned dogs with identical genomic backgrounds were selected as a drug detection dogs.…”
Section: Application Of Canine Scntmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on canine embryos are scarce because of difficulties in collecting in vivo‐produced embryos and the inability to produce canine embryos in vitro (Chastant‐Maillard et al., ). So far, no puppy has been obtained from an in vitro‐produced embryo; however, life births after cloning of somatic cells have been repeatedly reported in domestic dogs (Hossein et al., ; Lee et al., ; Oh et al., ) as well as in coyotes and wolves (Hwang et al., ; Kim et al., ).…”
Section: Art In Dogs Cats and Other Carnivores – State Of The Artmentioning
confidence: 99%